Literature Study: Complementary Therapy in Stimulating the Development of Infants Aged 0–12 Months - Susmita Susmita; Juni Harista (The Journal General Health and Pharmaceutical Sciences Research, 2025)
The 0–12 month period is a critical phase in infant development, covering motor, cognitive, and emotional domains. Early stimulation has been proven to prevent developmental delays that may affect later life stages. Complementary therapies such as infant massage and baby gym are widely applied as non-pharmacological, safe, low-cost interventions that can be practiced at home by parents. To systematically review the scientific evidence regarding the effectiveness of complementary therapies in stimulating the development of infants aged 0–12 months. This literature study involved a review of articles published between 2018–2024 from PubMed and Google Scholar. Inclusion criteria included experimental and quasi-experimental studies evaluating the effect of complementary therapies (infant massage, baby gym, or others) on infant development. Six relevant studies were identified, including four on baby gym and two on infant massage. All studies reported significant improvements in gross motor development following intervention. Infant massage also showed additional benefits such as increased weight gain and enhanced mother-infant bonding. Complementary therapies such as infant massage and baby gym are effective and practical strategies for stimulating infant development. However, further research with more robust experimental designs is needed to strengthen the evidence base.